FORMASI DAN STRUKTUR GERAKAN SOSIAL PETANI [Studi Kasus Gerakan Reklaiming/ Penjarahan Atas Tanah PTNP XII (Persero) Kalibakar, Malang Selatan] - Wahyudi, Wahyudi (Jurnal Masyarakat dan Budaya, 2010)
This research was conducted in Ex-Dutch Plantation Kalibakar, in the south of Malangand had objective to analyze the formation and structure of peasant movement in Kalibakar. This research resulted understanding that peasant social movements are determined by: structural conduciveness, structural strain, growth and spread generalized belief, precipitating factors, participant activation and mobilization, social control, support of network movement, decision making arena, and social structure differentiation. Keywords: peasants movement, peasants social movement formation